THE INFLUENCE OF THE INFORMAL SECTOR BEFORE A CURRENCY EXCHANGE COMPANY - Gissell González del Puerto, Analía; Torres Villalba, Griselda; Susana Villalba Román, Edith (Revista Gênero e Interdisciplinaridade, 2023)
This research work is about the influence of the informal sector before foreign exchange companies. In Paraguay, specifically in Ciudad del Este, today there is a large number of people who are engaged in informal currency exchange on public roads, this problem is specifically focused on Avenida Adrián Jara in Ciudad del Este, in which there are several companies that are dedicated to currency exchange, which in a certain way are affected by the large number of people who provide the same service only informally. The main objective of this work was to describe the influence that the informal currency exchange generates before the formal companies that are dedicated to this item. The study had a qualitative approach, the explanatory level was used, interviews directed to the companies were used. Unfortunately, these companies have competition, which is even unfair, due to the ease with which the informal sector operates and, in most cases, they offer services without any type of control. At the end it was possible to verify that, being formally constituted, the companies enjoy full support from the entities to which they are subject, therefore, they offer benefits to their clients such as greater security and speed in their transactions, this in the long term establishes reliability and transparency links.